Near-Infrared Absorption of Fused Core-Modified Expanded Porphyrins for Dye-Sensitized Solar Cells - Cardenas-Jiron, G; Borges-Martinez, M; Pino-Rios, R; Urzua-Leiva, R; Granados-Tavera, K; Morales-Lovera, S; Montenegro-Pohlhammer, N (American Institute of Physics, 2023)
Photophysical, photovoltaic, and charge transport properties of fused core-modified expanded porphyrins containing two pyrroles, one dithienothiophene (DTT) unit, and 1-4 thiophenes (1-4) were inspected by using density functional theory (DFT) and time-dependent DFT. Compounds 1-3 have been investigated experimentally before, but 4 is a theoretical proposal whose photophysical features match those extrapolated from 1 to 3. They exhibit absorption in the range of 700-970 nm for their Q bands and 500-645 nm for their Soret bands. The rise of thiophene rings placed in front of the DTT unit in the expanded porphyrin ring causes a bathochromic shift of the longest absorption wavelength, leading to near-infrared absorptions, which represent 49% of the solar energy. All the systems show a thermodynamically favorable process for the electron injection from the dye to TiO2 and adsorption on a finite TiO2 model. The electron regeneration of the dye is only thermodynamically feasible for the smallest expanded porphyrins 1 and 2 when I−/I3− electrolyte is used. The charge transport study shows that for voltages lower than 0.4 V, junctions featuring pentaphyrin 1 and octaphyrin 4 are more conductive than those containing hexaphyrin 2 or heptaphyrin 3. The results showed that the four fused core-modified expanded porphyrins investigated are potential dyes for applications in dye-sensitized solar cells, mainly pentaphyrin 1 and hexaphyrin 2. Moreover, increasing the number of thiophene rings in the macrocycle proved fruitful in favoring absorption in the near-infrared region, which is highly desired for dye-sensitized solar cells. © 2023 Author(s).